Lawyers and the Public - Richmond, Maurice (Victoria University of Wellington Law Review, 1999)
The substance of this paper was delivered as a public lecture at the Victoria University College, Wellington, New Zealand. It was one of a series of public lectures given by professors and lecturers at that College to mixed audiences. The author, Lecturer (and later Professor) in Law, challenges the notion that "the legal profession is a parasite infesting in the community, and ought to be extirpated" by exploring the true function of a lawyer. It is argued that the duty of the lawyer is to protect and enforce justice by serving their function as officers of the Courts of New Zealand, and that the profession will continue as long as there remains injustice in the world.